Oriented cell division as a response to cell death and cell competition. - Li, W.; Kale, A.; Baker, N.E. (Current Biology, 2009)
The imaginal disc epithelia that give rise to the adult ectoderm of Drosophila can compensate to produce normal adult organs after damage. We looked at the local response to cell death by using two genetic methods to elevate cell death rates. During cell competition, sporadic cell death occurs predictably along the boundaries between populations of competing wild-type and "Minute" cells (M/+). Boundaries between M/+ and wild-type populations show an unusual degree of mixing, associated with mitotic reorientation of wild-type cells toward M/+ territory that they take over. Apoptosis of M/+ cells was the cue, and reoriented mitosis required the planar cell polarity genes dachsous, fat, and atrophin. Clones mutated for pineapple eye, an essential gene, elevate apoptosis by a noncompetitive mechanism. Mitosis was also reoriented near cells mutant for pineapple eye, likewise dependent on the planar cell polarity genes. These findings show that planar cell polarity genes are required for responses to cell death. Oriented mitosis may help maintain morphology as dividing cells replace those that have been lost.